Short communication: Resazurin reducing time as an indicator of Bradyrhizobium viable cell count - Lemos, E. G. M. [UNESP]; Carareto-Alves, L. M. [UNESP] (Springer Nature, 1998)
A method based on the use of resazurin (RSZ) is described to determine the number of viable Bradyrhizobium japonicum cells in culture medium. The observation of RSZ reduction can be done spectrophotometrically or visually. B. japonicum strains behaved differently when the reducing time was considered. This methodology can be used to determine the number of viable cells during the liquid culture stage of inoculant production.
Keywords: Bradyrhizobium japonicum; Cell count; Indicator viability; Resazurin; cell count; cut flower; resazurin; spectrometry; vaccination; Bradyrhizobium